Studi Korelasi Konsep Diri Dengan Keenderungan Perilaku Bullying - Wahyuni, Siti (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2025)
his study aims to determine the relationship between self-concept and the tendencyof bullying behavior in SMP Negeri 46 Palembang. This study uses quantitative methods withcorrelational methods. The population in this study were all VIII grade students of SMP Negeri 46Palembang, totaling 385 students, with a research sample of 100 samples. Data collection wastaken using simple random sampling technique. The data collection instrument was aquestionnaire that measured self-concept and bullying behavior tendencies. Data analysis wascarried out using the Pearson Product-Moment correlation test. The results showed that the levelof self-concept of students was in the moderate category with a percentage of 44% 44 students,while the level of bullying behavior tendencies was in the moderate category with a percentageof 36% 36 students. The correlation coefficient obtained shows a significant value of 0.267 0.05and a calculated r value of 0.112 r table 0.194, so it is concluded that there is no significantrelationship between self-concept and the tendency of bullying behavior.